Perancangan E-Business UKM Kerajinan Khas Daerah Kalimantan Tengah di Kota Palangka Raya - Mochammad Ichsan; Lili Rusdiana; Sam'ani Sam'ani; Ferdiyani Haris; Muhammad Haris Qamaruzzaman (Jurnal Sains Komputer dan Teknologi Informasi, 2022)
The design is one of the foundations in building an application or system. The need for design as a support can be illustrated through diagrams and user interfaces. This study uses Unified Modeling Language as a plot description using Microsoft Visio software and the user interface using Balsamiq Mockups software. The design is carried out in building e-business Small and Medium Enterprises typical crafts of Central Kalimantan in the City of Palangka Raya. The design presented illustrates the need for applications for visitors or customers who will visit e-business, members who have an account in order to access e-business, and admin for managing data in e-business